Clinical and pathological analysis of deaths from different SARS-CoV-2 coronavirus genotypes - M. A. Vashukova; V. А. Zinserling; N. Yu. Semenova; D. V. Baram; A. V. Fadeev; K. S. Komissarova; A. B. Komissarov; D. A. Lioznov (Журнал инфектологии, 2022)
The genotype of the SARS-CoV-2 virus pathogen plays an important role in the epidemiological and clinical characteristics of a new coronovirus infection. There are no published data on the morphological features of lesions caused by different virus genotypes.The aim of the study was to evaluate clinical, laboratory and morphological changes depending on the genotype of the SARS-CoV-2 virus.Materials and methods. A retrospective analysis of the medical records of 39 patients with COVID-19 with a severe course of the disease, which ended in death, who were hospitalized at the St. Petersburg State Budgetary Infectious Diseases Clinical Hospital named after S.P. Botkin” in 20202022. Clinical and laboratory characteristics were assessed, including determination of the virus genotype, levels of leukocytes, lymphocytes, alanine aminotransferase, creatinine, ferritin, C-reactive protein, D-dimer, interleukin-6. Macro- and microscopic changes were assessed, including immunohistochemical examination of the lungs and other organs using sera to CD14 68, 163, type 1 and 3 collagen. The preparations were digitized on a Panoramic scanner, morphometric studies were carried out using the SlideViewer program, including the quantitative determination of the content of CD68+ macrophages in 12 cases.Results. In all patients, the disease was complicated by the development of pneumonia, the majority had concomitant diseases (94.6%). The average time of hospitalization was 19.0±1.6 days, the average time of stay in the intensive care unit was 7.7±1.2 days. The analysis, depending on the genotype of the SARS-CoV-2 virus, showed a statistical difference between the age of patients, the length of stay in the intensive care unit and the level of lymphocytes. Differences in the average duration of hospitalization, the level of laboratory parameters were not revealed. Histopathological picture in all examined was approximately the same. The content of CD68+ macrophages per unit area in different genotypes did not differ, but varied significantly within the same genotype.Conclusion. Thus, it was not possible to identify significant differences between the changes caused by different genotypes of the new coronavirus, which can probably be explained by the fact that mutations do not include genome regions that are relevant to virulence factors, although further research is needed.